Chapter Declinazioni del concetto di comunità nel progetto bioregionale: verso il superamento della dicotomia comunità/società - De La Pierre, Sergio (Territori, 2023)
The 'telluric' crises sweeping the world today at various levels - starting with the failure of the 'globalisation utopia' - have their origin in a worldwide ecological crisis that makes old development models unworkable. The emerging alternative is visible in the widespread diffusion of new territorial communities, which represent a challenge both to development models based on economic 'monoculture' and to the modern era vision of the community principle, seen as a remnant of the past doomed to disappear. Thousands of experiences of new communities are increasingly taking responsibility for a new world narrative (new territories ecologically built, principle of plurality, centrality of new social subjects and their relations, non-hierarchical forms of self-government, over-local 'bioregional' openness) which challenges the 19th-century opposition between 'community' and 'society': multi-actor, multidimensional and transcalar communities will be no less than the future society.